Human factors engineering and ergonomics : a systems approach - Guastello, Stephen J. (CRC Press, Taylor & Francis Group, 2014)
"Preface This textbook is the outgrowth of teaching human factors engineering for 30 years to undergraduates. The course is an offering of the psychology department, just as it was decades ago when I was a student myself. The field of human factors psychology (or human factors engineering, or engineering psychology) has changed markedly during that time. Although it still stays true to its original concerns about the person-machine interface, it has expanded to include new developments in stress research, accident analysis and prevention, and nonlinear dynamic systems theory (how systems change over time), and some aspects of human group dynamics and environmental psychology. Computer technology has permeated every aspect of the human-machine system, and has only become more ubiquitous since the previous edition. The systems are becoming more complex, so it should stand to reason that theories need to evolve to cope with the new sources of complexity. It has been a challenge to find a textbook for the class under these conditions of technological change. At first, I found one that seemed just perfect with regard to the breadth and depth of coverage I was looking for. After a few years it only needed a supplementary reading or two to help out, but eventually it went out of print, never to return. The other textbook choices by that time had diverged greatly in how they characterized the scope of the field. One approach concentrated on tables and graphs for otherwise traditional topics. A second approach retrenched into the theories of cognitive psychology and focused less on the practical problems in human factors. Meanwhile, library shelves were filling up with books on human-computer interaction that were becoming progressively more dissociated"--Resumé vydavatele